2001
DOI: 10.1046/j.1523-1755.2001.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of renal phosphate leak among patients with calcium nephrolithiasis

Abstract: : A low TmPi is more frequently encountered in stone formers with a normal PTH concentration than in control subjects and is associated with a high urinary Ca excretion. The hypophosphatemia induced by a renal phosphate leak may predispose the subject to calcium stone formation by increasing the serum calcitriol level, calcium excretion, and urinary saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 18 publications
6
54
1
3
Order By: Relevance
“…The rationale for the latter study was based on the well-known finding that high-P i diets elicit a decrease in the renal production and serum concentration of 1,25(OH) 2 D (17). Moreover, we demonstrated that P i supplementation of Npt2 Ϫ/Ϫ mice over a 4-day period corrects renal 1␣OHase activity and the serum concentration of 1,25(OH) 2 D, as well as the associated hypercalciuria (22), which is a known risk factor for renal calcification (18,19). In the present study, we report that both 1␣OHase gene ablation and P i supplementation lead to a significant reduction in urinary Ca excretion and a dramatic decrease in renal calcification in Npt2 Ϫ/Ϫ mice.…”
Section: In Npt2supporting
confidence: 66%
See 1 more Smart Citation
“…The rationale for the latter study was based on the well-known finding that high-P i diets elicit a decrease in the renal production and serum concentration of 1,25(OH) 2 D (17). Moreover, we demonstrated that P i supplementation of Npt2 Ϫ/Ϫ mice over a 4-day period corrects renal 1␣OHase activity and the serum concentration of 1,25(OH) 2 D, as well as the associated hypercalciuria (22), which is a known risk factor for renal calcification (18,19). In the present study, we report that both 1␣OHase gene ablation and P i supplementation lead to a significant reduction in urinary Ca excretion and a dramatic decrease in renal calcification in Npt2 Ϫ/Ϫ mice.…”
Section: In Npt2supporting
confidence: 66%
“…Our data support the hypothesis that the adaptive increase in serum 1,25(OH) 2 D, in response to hypophosphatemia, serves as a trigger for the cascade of events leading to the development of renal mineral deposits in Npt2 Ϫ/Ϫ mice. Moreover, our data are relevant to the finding that a significant proportion of stone-forming patients with hypercalciuria exhibit hypophosphatemia, secondary to a decrease in renal tubular P i reabsorption (18).…”
Section: Discussionmentioning
confidence: 78%
“…This disease is often referred to as IH because of increased intestinal absorption of calcium, and it can be associated with a mild renal phosphate leak, despite the lack of parathyroid hyperactivity. 38 Association of increased 1,25(OH) 2 D levels with renal calcifications was observed in mouse models that lack Fgf23 39 or Klotho 40 or individuals with CYP24A1 mutations, 35 even in the setting of low or normal urinary phosphate excretion. Finally, excessive phosphaturia, even with normal or low urinary calcium, can cause nephrocalcinosis in humans as is seen in XLH 41 or in phosphate enema-induced nephrocalcinosis.…”
Section: Serum 125(oh) 2 D Phosphate and Trp May Be Predictors Of mentioning
confidence: 99%
“…To pursue this question, Prie et.al. [31] studied 207 calcium stone formers with normal PTH levels and compared them to 105 normal subjects of similar age (although there was a higher percentage of females among the normals, 53% vs. 31% of the stone formers). The stone formers of both sexes had a significantly decreased renal phosphate threshold (TmPi) compared to normal subjects; values were normally distributed, but shifted to lower values among the stone formers.…”
Section: Renal Mineral Handling In Ihmentioning
confidence: 99%